From concepts to comparisons: A resource for diagnosis and measurement in social-ecological systems. Issue 107 (May 2020) - Cox, Michael; Villamayor-Tomas, Sergio; Ban, Natalie C.; Epstein, Graham; Evans, Louisa; Fleischman, Forrest; Nenadovic, Mateja; Lopez, Gustavo A Garcia; van Laerhoven, Frank; Meek, Chanda; Ibarra, Irene Perez; Schoon, Michael
Abstract: A central challenge facing the study the environmental governance is the lack of commonunderstanding of important concepts. Critical concepts such as social boundaries, property rights, and resource dependence are selected and measured inconsistently across research projects and field settings, producing results that are difficult to compare. This stymies the accumulation of scientific evidence regarding the most effective ways to address challenging environmental problems. As members of the Social-ecological systems meta-analysis database (SESMAD) project, we have addressed this challenge by developing a repository of variables associated with many of the most important concepts across a range of fields related to environmental governance. In this paper we describe the infrastructure behind the repository, the range of variables it includes, and how it can enable scholars across a range of fields to more systematically select and measure the variables to include in their analyses. Highlights: Inconsistencies in variable selection and measurement limit social-ecological studies. These limitations relate to a suite of methodological challenges. A new variables repository helps users diagnose and measure key factors. Through this resource more comparable research can be done across cases.